The endocannabinoid, anandamide, induces cannabinoid receptor-independent cell death in renal proximal tubule cells - Schlosser, Monika; Löser, Heike; Siegmund, Sören V.; Montesinos-Rongen, Manuel; Bindila, Laura; Lutz, Beat; Barrett, David A.; Sarmad, Sarir; Ortori, Catharine A.; Grau, Veronika; von Brandenstein, Melanie; Fries, Jochen W.U. (Scientific Research Publishing, 2017)
Background: The endocannabinoid (EC) system is well characterized in the central nervous system but scarcely studied in peripheral organs. In this paper, we newly identify the effect of the EC anandamide (AEA) upon renal proximal tubule cells. Methods: Measurement of lactate dehydrogenase (LDH) release after treatment of primary renal proximal tubule cells (RPTEC) and renal carcinoma cell line (Caki-1) with AEA, arachidonic acid (AA), ethanolamide (EtAm), EC receptor CB1 antagonist (AM251), CB2 receptor antagonist (SR144528), TRPV1 receptor antagonist (capsazepine), degradation enzyme fatty acid amide hydrolase (FAAH) antagonist (URB597), antioxidants GSH-EE; Trolox, GSH depletor BSO, membrane cholesterol depletor (MCD), apoptosis inhibitor zVAD, necroptosis inhibitor Nec-1 or ferroptosis inhibitor Fer-1. Western blot and qRT-PCR analysis plus determination of reactive oxygen species (ROS) via H2-DCFDA were performed. Histology for EC enzymes, N-acetylphosphatidylethanolamine hydrolyzing phospholipase D (NAPE-PLD) and FAAH, as well as the determination of physiological levels of ECs in human and rat renal tissue via liquid chromatography were conducted. Results: AEA both dose- and time-dependently induces cell death in RPTEC and Caki-1 within hours, characterized by cell blebbing, not influenced by blocking the described EC receptors by AM251, SR144528, capsaze pine or FAAH by URB597 or MCD. Cell death is mediated via ROS. There is no difference found in the histology of the enzymes FAAH and NAPE-PLD in human renal tissue with interstitial nephritis. Blocking of apoptotic, necroptotic or ferroptotic cell death does not lead to a reduction in LDH release in vitro. Conclusion: The endocannabinoid anandamide induces cell death in renal proximal tubule cell in a time- and dose-dependent manner. This pathway is mediated via ROS and is independent of cannabinoid receptors, membrane cholesterol or FAAH activity.